2022
DOI: 10.1021/acs.jpcc.2c04720
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Pt Shell Bearing Tensile Strain Still Have Superior Activity for the Oxygen Reduction Reaction?

Abstract: Nanoparticles with a 55 nm Au core and a few monolayers of Pt shell (denoted as Au@Pt x ML, x = 1–4) are found to have superior activity toward the oxygen reduction reaction (ORR) compared to commercial Pt nanoparticles and polycrystalline Pt (pc-Pt) electrodes in 0.1 M HClO4. The half-wave potential for ORR at Au@Pt1 ML is ca. 20 mV positively shifted. With the decrease of the Pt shell thickness from 4 to 1 monolayer, both the extent of enhancement of the ORR activity and the adsorption strength of oxygen-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…16−18 This strategy has been successfully applied to in situ study the ORR mechanism of Pt-based catalysts, and direct spectral evidence of oxygencontaining adsorbents such as *OOH has been observed. 19,20 However, the evolution of the *OOH adsorption configuration has yet to be reported. Herein, the borrowing strategy was prolonged to study the configuration change of surface adsorbents on Pt-based alloys during ORR (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16−18 This strategy has been successfully applied to in situ study the ORR mechanism of Pt-based catalysts, and direct spectral evidence of oxygencontaining adsorbents such as *OOH has been observed. 19,20 However, the evolution of the *OOH adsorption configuration has yet to be reported. Herein, the borrowing strategy was prolonged to study the configuration change of surface adsorbents on Pt-based alloys during ORR (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy (SERS) is a highly sensitive technique for detecting surface oxygen-containing species, especially in the low wavenumber region. , The extended SERS “borrowing” strategy based on core–shell nanoparticles (NPs) broke the limit of traditional SERS technology on the universality of the substrate and greatly expanded the application scope of SERS. This strategy has been successfully applied to in situ study the ORR mechanism of Pt-based catalysts, and direct spectral evidence of oxygen-containing adsorbents such as *OOH has been observed. , However, the evolution of the *OOH adsorption configuration has yet to be reported. Herein, the borrowing strategy was prolonged to study the configuration change of surface adsorbents on Pt-based alloys during ORR (Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, palladium has been widely used as a substrate for platinum deposition in core–shell catalysts due to their close lattice match, and both theoretical and experimental studies have shown that the activity can be enhanced as a result of electronic coupling between Pd and Pt. Another strategy for obtaining a decent ORR performance in platinum would be hindering its shape to some specific facets and optimizing the surface structure through shape-controlled synthesis, as ORR is a structure-sensitive reaction. , The specific activity of Pd@Pt core@shell catalyst has shown to increase in the order of (100) < (110) < (111). In all cases, the Pt d-band center will be downshifted, resulting in reduced oxygen binding energy on platinum. Stamenkovic et al have demonstrated that the d-band center has an optimum value, and the highest specific activity follows a volcano plot in relation to oxygen binding energy. , Despite the sole incorporation of all these techniques in previous studies and reports showcasing the successful synthesis of Pt-based catalysts with remarkable activity toward ORR, practical use is still confined due to their low durability in the corrosive operating conditions of ORR. The low durability is mainly attributed to the thermodynamically unstable structures, which are necessary for highly active catalysts, but result in rapid performance losses.…”
Section: Introductionmentioning
confidence: 99%
“…6 For that, it is necessary to understand the ORR mechanism and factors that affect ORR kinetics on the electrocatalysts. 7 However, the complex catalyst structure in practical electrode materials limits the in-depth study of ORR kinetics. 8−10 Singlecrystal electrodes with well-defined surfaces and a controlled atomic arrangement 11−18 are of great help in elucidating the reaction mechanism and unraveling the structure−activity relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolyte membrane fuel cells (PEMFCs) are promising technologies for the extensive use of sustainable energy due to their high energy conversion efficiency and the wide range of potential applications with different power density scales. However, the high overpotential of oxygen reduction reaction (ORR) at the cathode of PEMFCs requires a high loading of precious Pt group catalysts which limits large-scale application. , Thus, developing cathode catalysts with high electrocatalytic activity is of significant importance . For that, it is necessary to understand the ORR mechanism and factors that affect ORR kinetics on the electrocatalysts . However, the complex catalyst structure in practical electrode materials limits the in-depth study of ORR kinetics. Single-crystal electrodes with well-defined surfaces and a controlled atomic arrangement are of great help in elucidating the reaction mechanism and unraveling the structure–activity relationship.…”
Section: Introductionmentioning
confidence: 99%